Customer Satisfaction on Online Banking Services at Present Scenario in India - Dr. K. Ganesamurthy, Mr. Rajendran (International Journal of Advanced Science and Technology, 2019)
The banking industry like many other financial services industries is facing a rapidly changing market, new technologies, economic uncertainties, fierce competition, and especially more demanding customers; and the changing climate has presented an unprecedented set of challenges. The Banking sectors have been elevating the role of the customer to that of a key stakeholder. Customers are viewed as a group by the banks and satisfaction of the customers with their business must be incorporated in strategic planning efforts. Forward-looking banking institutions are finding value in directly measuring and tracking satisfaction level of their customer as an important strategic success indicator to sustain in the market and achieve further growth. Hence, the present study is undertaken to explore the customers’ satisfaction and factors which are influencing to determine the customers’ satisfaction as the study of this kind will give many implications to the relevant people in the banking industry and help them to devise appropriate policy to offer better services online to its customers at commercial banks in Tamilnadu.Key Words: Customer satisfaction, technology; economic; market; banking industry